Point‐of‐care diagnostic assay for rapid detection of porcine deltacoronavirus using the recombinase polymerase amplification method. Issue 3 (1st April 2019) - Ma, Lei; Zeng, Fanwen; Huang, Bihong; Zhu, Yujun; Wu, Miaoli; Xu, Fengjiao; Xiao, Li; Huang, Ren; Ma, Jingyun; Cong, Feng; Guo, Pengju
Summary: Porcine deltacoronavirus (PDCoV) has emerged and spread throughout the porcine industry in many countries over the last 6 years. PDCoV caused watery diarrhoea, vomiting and dehydration in newborn piglets. A sensitive diagnostic method would be beneficial to the prevention and control of PDCoV infection. Recombinase polymerase amplification (RPA) is an isothermal amplification method which has been widely used for virus detection. A probe‐based reverse transcription RPA (RT‐RPA) assay was developed for real‐time detection of PDCoV. The amplification can be finished in 20 min and fluorescence monitoring was performed by a portable device. The lowest detection limit of the PDCoV RT‐RPA assay was 100 copies of RNA molecules per reaction; moreover, the RT‐RPA assay had no cross‐reaction with other common swine viruses. The clinical performance of the RT‐RPA assay was evaluated using 108 clinical samples (54 intestine specimens and 54 faecal swab specimens). The coincidence rate of the detection results for clinical samples between RT‐RPA and RT‐qPCR was 97.2%. In summary, the real‐time RT‐RPA assay offers a promising alternative to RT‐qPCR for point‐of‐care detection of PDCoV.